Effect of Ethepon as Ripening Stimulant on The Tamarillo Fruit with Two Maturity Levels - Rosdiana Rosdiana; Elisa Julianti; Lasma Nora Limbong (Universitas Sumatera Utara, 2014)
Posharvest handling is an attemp to meet market demand of ideal agricultural products condition. The aim of this research was to find the effect of ethepon as ripening stimulant on the tamarillo fruit with two maturity levels. The research had been performed using completely randomized design with two factors, i.e the maturity of tamarillo fruit (M) : (green and green to yellow) and ethepon concentration (E) : (0 ppm, 250 ppm, 500 ppm and 750 ppm). Parameters observed were moisture content, weight loss, vitamin C content, hardness, titratable acidity, total soluble solid, maturity index, color score, organoleptic values of color, flavor and texture. The results showed that maturity level had highly significant effect on moisture content, weight loss, vitamin C content, hardness, titratable acidity, total soluble solid, maturity index, color score, organoleptic values of color, flavor and texture. The ethepon concentration had highly significant effect on moisture content, weight loss, hardness, titratable acidity, total soluble solid, maturity index, color score, organoleptic values of color, flavor and texture. Interaction of the two factors had highly significant effect on hardness, maturity index, color score and organoleptic value of color. The green to yellow maturity of tamarillo and 750 ppm concentration of ethepon produced the best quality of tamarillo at seven days storage. Keywords : ethepon concentration, maturity level, tamarillo